2017
DOI: 10.1117/1.nph.4.3.035001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ischemic stroke induction and mesoscopic imaging assessment of blood flow and ischemic depolarization in awake mice

Abstract: Despite advances in experimental stroke models, confounding factors such as anesthetics used during stroke induction remain. Furthermore, imaging of blood flow during stroke is not routinely done. We take advantage of bihemispheric transcranial windows for longitudinal mesoscopic imaging of cortical function to establish a protocol for focal ischemic stroke induction in target brain regions using photothrombosis in awake head-fixed mice. Our protocol does not require any surgical steps at the time of stroke in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…However, to date, there are only several proof-of-principle studies utilizing this approach, and they only employ Ca 2+ sensors of the GCaMP family. Murphy and colleagues have developed a protocol of focal stroke induction in awake head-fixed mice combined with laser speckle contrast imaging blood flow assessment and mesoscopic wide-field Ca 2+ imaging through bihemispheric transcranial windows [391]. Using transgenic GCaMP3 mice, they were able to directly observe the ischemic depolarizing wave within 5 min of stroke induction.…”
Section: Animal Models For Real-time Imaging Of Cell Signaling and Mementioning
confidence: 99%
“…However, to date, there are only several proof-of-principle studies utilizing this approach, and they only employ Ca 2+ sensors of the GCaMP family. Murphy and colleagues have developed a protocol of focal stroke induction in awake head-fixed mice combined with laser speckle contrast imaging blood flow assessment and mesoscopic wide-field Ca 2+ imaging through bihemispheric transcranial windows [391]. Using transgenic GCaMP3 mice, they were able to directly observe the ischemic depolarizing wave within 5 min of stroke induction.…”
Section: Animal Models For Real-time Imaging Of Cell Signaling and Mementioning
confidence: 99%
“…Photothrombotic stroke was induced by injecting 10 mg/ml of Rose Bengal intraperitoneally 5 minutes prior to 20 minutes green laser (532 nm wavelength at power 10 mW) illumination at the thinned region as previously described [38][39][40] . The thinned area was covered with dental cement.…”
Section: Analysis Of Lfpsmentioning
confidence: 99%
“…Previous studies, albeit under anesthesia, have shown the ability to occlude surface arterioles or individual penetrating arterioles using photothrombosis by controlling the parameters of laser illumination in order to minimize photodamage to adjacent and deeper vessels. [26][27][28] Although photothrombosis has been performed in awake animals 29 and has also been used to target individual vessels, 26 these methods have not been previously combined. Here we combine the benefits of formerly used techniques to create a chronically prepared mouse photothrombosis stroke model that induces targeted ischemic stroke in awake mice while simultaneously monitoring macroscopic changes to CBF.…”
Section: Introductionmentioning
confidence: 99%